Basic process control series (Clarity Multimedia)
This intensive nine-part CD-ROM series covers every aspect of instrumentation and its many applications. Beginning with the principles and concepts of process control - with a special emphasis on maintenance skills - the series covers calibration, replacement, repair adjustment, and troubleshooting in great detail.